Gestão, informação e comunicação museológica: um estudo comparativo entre pequenos e médios museus brasileiros e franceses - Vania Carvalho Rola Santos (2011)
Thesis elaborated on the basis of a comparative study, which used the exploratory research, through the application of a survey to Brazilian and French museums. There were selected museums from allregions of Brazil and French, from north to south, east to west. In this thesis, the museum is perceived as an unit of information and communication, and the choice of the type of museum to study waspurposely directed to units with small to medium sized technical and administrative structure, museums that are not part of the major touristic rote and don't have any media visibility. In part, the choice was determined by the interest and experience of the thesis' author in the museums theme, as well as the fact that museums of small size have not been a recurrent object of study over the years and don't receive much attention from the academic researches. Therefore, both recent graduated and experienced museologists have a lack of references from studies directed to this type of institution. The museum was, at first, approached as unit of information, based on the theoretical concepts ofauthors from the Information Science field, as GUINCHAT & MENOU. Then, this understanding was expanded, conceiving the museum as unit of information and communication, with the theoretical foundation of authors such as Tobelem and Davallon. The results of the survey were analyzed and divided into two blocks: Museum Management and Museological Information and Communication. Theanalysis was made based on concepts of the scientific and conceptual fields from Museology and of the Information Science, seeking to observe the interaction and integration of the scientific and the practical areas. It was found that the museums analyzed, in most cases, were public institutions, being characterized as a public service, which have, as primary mission, the custody and safeguarding of cultural heritage of their country. It was also found that the differences between Brazilian and French museums, observed in this study, are not so expressive, that the museum management model and the processes of information and communication in both countries are very similar, because the cultural policies of the museum field are defined by organizations such as UNESCO and ICOM, of which Brazil and France are both part. The biggest difference found between Brazilian and French museums is in the model of how the public administration works on each country, which is morecentralized in France, due to the fact that in the political and historical construction of France the federal level has always shown a strong tendency to impose and dictate more strongly the norms and rules to be followed by states and municipalities, contrary to what occurs in the Brazilian public administration, as these have greater autonomy of action.